Multilocus phylogenetic analysis of the first molecular data from the rare and monotypic Amarsipidae places the family within the Pelagia and highlights limitations of existing data sets in resolving pelagian interrelationships - Campbell, Matthew A.; Sado, Tetsuya; Shinzato, Chuya; Koyanagi, Ryo; Okamoto, Makoto; Miya, Masaki (Molecular Phylogenetics and Evolution, 2018)
[Display omitted] •The Pelagia is a recently recognized taxon of open ocean fishes.•We provide evidence that Amarsipidae is a pelagian family.•Support for early-branching nodes is low in molecular phylogenies of Pelagia.•Refinement of pelagian interrelationships requires new independent data sets.•The age and speed of the pelagian radiation may prevent total resolution. The Pelagia is a recently delineated group of fishes, comprising fifteen families formerly placed in six perciform suborders. The Pelagia was lately recognized as it encompasses huge morphological diversity and only in the last few years have large-scale molecular phylogenetic studies been undertaken that could unite such morphologically disparate lineages. Due to the recent erection of Pelagia, the composition of the taxon is not entirely certain. Five families of the former perciform suborder Stromateoidei have been identified as pelagians. However, the sixth stromateoid subfamily Amarsipidae is a rare monotypic family that has distinctive meristic and morphological characteristics from that of other stromateoids such as the lack of a pharyngeal sac. We examine molecular data generated from the sole species in Amarsipidae, Amarsipus carlsbergi, and demonstrate that it is clearly nested within Pelagia. As with two previous studies that have the breadth of sampling to evaluate pelagian intra-relationships, we find high support for monophyly of most family-level taxonomic units but statistical support for early-branching nodes in the pelagian tree is very low. We conduct the first analyses of Pelagia incorporating the multispecies coalescent and are limited by a high degree of missing loci, or, incomplete taxon sampling. The high degree of missing data across a complete sampling of pelagian lineages along with the deep time scale and rapid radiation of the lineage contribute to poor resolution of early-branching relationships within Pelagia that cannot be resolved with current data sets. Currently available data are either mitochondrial genomes or a super matrix of relatively few loci with a high degree of missing data. A new and independent dataset of numerous phylogenetic loci derived from high-throughput sequencing technology may reduce uncertainty within the Pelagia and provide insights into this adaptive radiation.